New physics explanations of aμ in light of the FNAL muon g − 2 measurement - Athron, Peter; Balázs, Csaba; Jacob, Douglas H. J.; Kotlarski, Wojciech; Stöckinger, Dominik; Stöckinger-Kim, Hyejung (The journal of high energy physics, 2021)
A bstract The Fermilab Muon g − 2 experiment recently reported its first measurement of the anomalous magnetic moment a μ FNAL , which is in full agreement with the previous BNL measurement and pushes the world average deviation ∆ a μ 2021 from the Standard Model to a significance of 4 . 2 σ . Here we provide an extensive survey of its impact on beyond the Standard Model physics. We use state-of-the-art calculations and a sophisticated set of tools to make predictions for a μ , dark matter and LHC searches in a wide range of simple models with up to three new fields, that represent some of the few ways that large ∆ a μ can be explained. In addition for the particularly well motivated Minimal Supersymmetric Standard Model, we exhaustively cover the scenarios where large ∆ a μ can be explained while simultaneously satisfying all relevant data from other experiments. Generally, the a μ result can only be explained by rather small masses and/or large couplings and enhanced chirality flips, which can lead to conflicts with limits from LHC and dark matter experiments. Our results show that the new measurement excludes a large number of models and provides crucial constraints on others. Two-Higgs doublet and leptoquark models provide viable explanations of a μ only in specific versions and in specific parameter ranges. Among all models with up to three fields, only models with chirality enhancements can accommodate a μ and dark matter simultaneously. The MSSM can simultaneously explain a μ and dark matter for Bino-like LSP in several coannihilation regions. Allowing under abundance of the dark matter relic density, the Higgsino- and particularly Wino-like LSP scenarios become promising explanations of the a μ result.